Validity of E-module Based on Cognitive Conflict Integrated Augmented Reality for Improving Students Physics Science Literacy - Wulanda Tri Emilya; Fatni Mufit (Postgraduate, University of Mataram, 2023)
Achieving 21st century skills is anticipated by managing learning based on scientific literacy. This literacy is the life skills of students, so they can solve existing problems by collaborating in thinking scientifically. Scientific literacy is defined as an understanding of the characteristics of science as a form of knowledge, awareness, intellect, and culture that involves science. Low science learning can be indicated by students' low scientific literacy. To increase students' scientific literacy, a learning model that supports this is needed. One learning model that can be used is the cognitive conflict-based learning model. Considering the phenomena and demands of students, researchers want to develop an e-module based on cognitive conflict integrated with augmented reality to increase students' physical literacy in physics materials. The type of research conducted was Design Research (Design Research). The development model used in this study was the Plomp model. The data analysis technique used a validation sheet questionnaire, analyzed using presentation techniques, and the V-Aiken formula. The results of data analysis obtained a validity value of 0.93 with the valid category, this was obtained because the e-module developed was in accordance with material substance, learning design, visual communication display, and software utilization. Â